On the issue of acid treatment of the well bottomhole; Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 336, № 11 - Ismayilov Sh. Z. Shahin Ziraddin (2025, 2025)
Relevance. The need to understand the features of reservoir and well interaction. To solve a number of scientific and engineering problems, it is currently necessary to stabilize the flow rate. World practice shows that many deposits in Siberia, Canada, Mexico, Venezuela are represented by heavy oils, which contain a significant amount of paraffins, resins and asphaltenes. When the temperature at the bottomhole decreases, the sedimentation of these components negatively affects the filtration and capacity properties. They are soluble in acid solutions, resulting in positive effect, which consists in increasing the efficiency of bottomhole zone treatment, as an aftermath of which the productivity of wells increases, which is an important task in the context of rising prices for hydrocarbons. Therefore, a more efficient use of the existing well stock, which, in comparison with drilling new wells, is the most rational from an economic point of view is realized. Aim. Theoretical substantiation using hydrodynamic modeling, which allows estimating the duration of acid treatment and efficiency in terms of increasing productivity. Mathematical calculation of the specified characteristics based on initial formation and well data. Using modern methods of perforation, acid treatment of the bottomhole zone, it is possible to stabilize or increase oil production by affecting the bottomhole of production wells. Methods. Mathematical modeling based on the course of underground hydromechanics and static methods. Results and conclusions. The conducted mathematical analysis allows determining the main parameters of the solution injected into the well. Based on the data of the calculation formulas it is possible to determine the time of injection to stabilize the parameters of the formation. The proposed work has a special practical value, since acid treatment increases productivity by 10–20%, which in these conditions even with a small well flow rate is significant. With the given parameters, production was 3.5 t/day, after the acid treatment, an increase in the filtration and capacity characteristics of the bottomhole zone by 17% is observed